Bullwhip Effect Intensity in Automotive Industry: Short Loop Supply Chain Case Study - Attila TURI (Communications of International Proceedings, 2021)
The goal of the paper was to analyze data from a short loop supply chain (supplier – manufacturer – customer) and see if a bullwhip effect was present, as well as to quantify its intensity within a case study from an automotive industry company based in Western Romania. Research data was gathered and analyzed within a period of 17 weeks for the case of one specific customer (4 different models of the same car brand) and 10 of the manufacturing site’s most important suppliers. Results confirm the existence of a bullwhip effect, as there is an almost 14% difference in variation between the group of analyzed suppliers and customers, an almost 17% extra variation for supplier orders when comparing the extremities of the average order variation and the refined difference between supplier orders (more than 14%) being significantly higher than those from customers (around 1%). Conclusions thus show the presence of a bullwhip effect, but its intensity can be reduced by up to 50% by improving internal performance metrics whilst also increasing supplier-manufacturer integration in upstream and downstream supply chain material and information flows.
Keywords: Demand Variation; Logistics Performance Metrics; Order Fluctuation; Supply Chain Integration